Relationship between body mass index and postural balance among student of the martial arts club malikussaleh university - Melina Handayani; Muhammad Sayuti; Cut Sidrah Nadira (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Relationship between body mass index and postural balance among student of the martial arts club malikussaleh university. Postural balance is an important component in martial arts. Every player martial art needs fast and strong movements so that the body must be well controlled. Disturbances such as body mass index (BMI) that are not ideal can affect postural stability. The height and shortness or the weight and lightness of a person will affect the location of the center of gravity that later will affect the balance. The purpose of this study is to find out the relationship between body mass index and postural balance among students of the Martial Arts Club Malikussaleh University. This study used a cross-sectional design which was conducted in March 2021 at the Bukit Indah Campus, Malikussaleh University. The sample of this study used total sampling with 49 respondents. Data collection was carried out by measuring body weight, height, static balance with a standing stork test and dynamic balance with a modified bass test of dynamic balance. The results of this study obtained BMI with the highest proportion is normal category, with 31 people (63.3%), while the static balance commonly found in the very good category with 11 people (22.4%), and dynamic balance commonly found in the balanced category with 29 people (59.2 %). The results of the chi-square analysis showed that there was a relationship between BMI with static balance (p = 0.019) and dynamic balance (p = 0.012). This study concludes that there is a relationship between BMI and postural balance among students of Martial Arts Club Malikussaleh University.